Antitoxic Immunity in Experimental Cholera: Observations with Purified Antigens and the Ligated Ileal Loop Model - Finkelstein, Richard A. (1970)
Rabbits immunized with purified antigens, choleragen and choleragenoid (cholera exo-enterotoxin and natural toxoid), were found to resist intra-intestinal challenge with a variety of strains of cholera vibrios. The resistance occurred in the absence of a significant antibacterial antibody response. In fact, the antigens were incapable of protecting mice against the septicemic infection of the standard mouse protection test used for bioassay of conventional cholera vaccines. The immunized rabbits did, however, develop a significant antitoxin titer demonstrable by passive hemagglutination, although the presence of antitoxic coproantibody could not be established conclusively. The results suggest the potential value of antitoxic immunity in cholera and are consistent with the existence of only one serological type of cholera exo-enterotoxin.